2016
DOI: 10.35790/ecl.4.1.2016.11686
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan obesitas pada kehamilan dengan preeklampsia

Abstract: This study aimed to obtain the relationship between obesity in pregnancy and preeclampsia. This was a retrospective analytical study with a case-control design by using data of patients’ medical records. Samples were pregnant women with obesity (IMT ≥30 kg/m2) at the last pregnancy that suffered from preeclampsia and obese pregnant women without preeclampsia at RSUP Prof. Dr. R. D. Kandou Manado from January, 2013 until December 2014. Data were processed by using SPSS 2.0. The results showed that the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
4
0
3
Order By: Relevance
“…Our finding is consistent with a number of studies conducted in Manado -Indonesia, Cairo and the US. 6,8,17,18 However, a case control study conducted in Padang, West Sumatera found that there was no association between obesity and pre-eclampsia. 15 The setting of this study was at the Padang District Hospital, which allows coordinated services across departments to screen high risk pregnancy and non-communicable diseases including obesity during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is consistent with a number of studies conducted in Manado -Indonesia, Cairo and the US. 6,8,17,18 However, a case control study conducted in Padang, West Sumatera found that there was no association between obesity and pre-eclampsia. 15 The setting of this study was at the Padang District Hospital, which allows coordinated services across departments to screen high risk pregnancy and non-communicable diseases including obesity during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Suatu penelitian oleh Anjel di Amerika Serikat pada wanita usia subur menunjukkan bahwa 24,5% wanita usia 20-44 tahun memiliki status gizi overweight dan 23% di antaranya obesitas. (Dumais et al, 2016) Obesitas pada ibu hamil adalah peningkatan berat badan yang kelewat batas,yang melebihi peningkatan standart berat badan ibu hamil yaitu 10-15 kg. Wanita hamil memiliki berat badan yang berlebih atau obesitas beresiko cukup besar pada masa kehamilan hingga masa melahirkan.…”
Section: Pendahuluanunclassified
“…Whereas the condition of not preeclampsia is more experienced by mothers who are not obese (88.9%) when compared to obese mothers (62.4%). In accordance with the research conducted at RSUP Prof. dr. R. D. Kandou Manado which shows an association between obesity and the incidence of preeclampsia [11].…”
Section: Relationship Between Obesity In Pregnant Women Andmentioning
confidence: 99%